The Hospital : life, death, and dollars in a small American town - Alexander, Brian (New York : St. Martin's Press, 2021)
"An intimate, heart wrenching portrait of one small hospital that reveals the magnitude of America's health care crises. By following the struggle for survival of one small-town hospital, and the patients who walk, or are carried, through its doors, The Hospital takes readers into the world of the American medical industry in a way no book has done before. Americans are dying sooner, and living in poorer health. Alexander argues that no plan will solve America's health crisis until the deeper causes of that crisis are addressed. Bryan, Ohio's hospital, is losing money, making it vulnerable to big health systems seeking domination and Phil Ennen, CEO, has been fighting to preserve its independence. Meanwhile, Bryan, a town of 8,500 people in Ohio's northwest corner, is still trying to recover from the Great Recession. As local leaders struggle to address the town's problems, and the hospital fights for its life amid a rapidly consolidating medical and hospital industry, a 39-year-old diabetic literally fights for his limbs, and a 55-year-old contractor lies dying in the emergency room. With these and other stories, Alexander strips away the wonkiness of policy to reveal Americans' struggle for health against a powerful system that's stacked against them, but yet so fragile it blows apart when the pandemic hits. Culminating with COVID-19, this book offers a blueprint for how we created the crisis we're in"--.
new book 2022 fall.
Includes bibliographical references and index.
Keywords: Public health -- United States; Public health -- United States -- Finance; Public health administration -- United States